2001
DOI: 10.1152/ajpheart.2001.280.2.h705
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+activation of myofilaments from transgenic mouse hearts expressing R92Q mutant cardiac troponin T

Abstract: The functional consequences of the R92Q mutation in cardiac troponin T (cTnT), linked to familial hypertrophic cardiomyopathy in humans, are not well understood. We have studied steady- and pre-steady-state mechanical activity of detergent-skinned fiber bundles from a transgenic (TG) mouse model in which 67% of the total cTnT in the heart was replaced by the R92Q mutant cTnT. TG fibers were more sensitive to Ca(2+) than nontransgenic (NTG) fibers [negative logarithm of half maximally activating molar Ca(2+) (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 45 publications
10
96
0
1
Order By: Relevance
“…In a few cases, some FHC mutants show no change in Ca 2ϩ sensitivity. Fiber studies in transgenic mice harboring the TnT-FHC mutations (I79N and R92Q) also show increased Ca 2ϩ sensitivity, which possibly leads to altered cardiac energetics through increased cost of force production in vivo (29,30). In addition to changes in Ca 2ϩ sensitivity, FHC TnT mutations lead to alterations in ATPase activity, troponin solubility and folding, thin filament sliding speed, and the Ca 2ϩ affinity of troponin C (27,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…In a few cases, some FHC mutants show no change in Ca 2ϩ sensitivity. Fiber studies in transgenic mice harboring the TnT-FHC mutations (I79N and R92Q) also show increased Ca 2ϩ sensitivity, which possibly leads to altered cardiac energetics through increased cost of force production in vivo (29,30). In addition to changes in Ca 2ϩ sensitivity, FHC TnT mutations lead to alterations in ATPase activity, troponin solubility and folding, thin filament sliding speed, and the Ca 2ϩ affinity of troponin C (27,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of cTn Exchange by Western Blot-Recombinant TNT in the present study included an NH 2 terminus myc tag to allow for quantification of the amount of cTn exchange by Western blotting techniques (17,18). Previously, our group has demonstrated that the presence of this myc tag does not affect myofilament function (17).…”
Section: Methodsmentioning
confidence: 99%
“…The expression and purification of the recombinant human cardiac TNT containing an NH 2 -terminal myc tag was carried out as previously described with slight modification of the purification protocol (17,18). Reconstitution and purification of intact Tn complex was carried out by sequential dialysis to remove urea and decrease salt of an equimolar amount of purified cTn components and purification using Resource-Q (1 ml; Amersham Biosciences) (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis of Recombinant Troponin ExchangeThe Western blot method to measure the extent of recombinant troponin exchange has been previously reported (40). Briefly, isolated skinned myocytes were exchanged overnight with recombinant troponin and after twice resuspending in relaxing solution myocytes were solubilized in 8 M Tris-urea denaturing buffer, and Laemmli buffer was added.…”
Section: Methodsmentioning
confidence: 99%
“…The exchange efficiency was calculated as the percentage ratio of exogenous myc-cTnT (top band) relative to total cTnT (top ϩ bottom band), which was quantified using the ImageJ gel densitometry analysis toolkit. The presence of the myc-tag on cTnT has been shown to not affect the cardiac force- [Ca 2ϩ ] relationship (40). Isometric Force Measurement-Permeabilized (skinned) myocytes in relaxing solution were placed in a 0.1% BSA-coated 35-mm culture dish on the stage of an inverted microscope (Leica DMIRB).…”
Section: Methodsmentioning
confidence: 99%